2013
DOI: 10.3997/1873-0604.2013065
|View full text |Cite
|
Sign up to set email alerts
|

3D effects on 2D resistivity monitoring in earth‐fill dams

Abstract: Measuring resistivity is a potentially powerful method of monitoring leakage zones that have developed in a dam, and their expansion over time. Generally, for embankment dams, two-dimensional (2D) resistivity data have been measured along the dam crest for the detection of leakage zones. However, the three-dimensional (3D) effects created by specific dam geometry and fluctuations in reservoir water levels significantly distort the 2D resistivity data measured at the dam crest. This study evaluates the 3D effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…On one hand, their inner structure may exhibit strong longitudinal and transverse variability (e.g., presence of a clay core or repaired zones). On the other hand, embankment topography and high water‐level fluctuations adjacent to the dike have 3D effects on the resistivity measurements leading to image artefacts (Hennig, Weller, and Canh ; Sjödahl, Dahlin, and Zhou ; Oh ; Fargier et al ; Cho et al ). In order to account for the full 3D attributes of the problem, one would normally recommend the use of a complete 3D ERI procedure (e.g., Chambers et al ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On one hand, their inner structure may exhibit strong longitudinal and transverse variability (e.g., presence of a clay core or repaired zones). On the other hand, embankment topography and high water‐level fluctuations adjacent to the dike have 3D effects on the resistivity measurements leading to image artefacts (Hennig, Weller, and Canh ; Sjödahl, Dahlin, and Zhou ; Oh ; Fargier et al ; Cho et al ). In order to account for the full 3D attributes of the problem, one would normally recommend the use of a complete 3D ERI procedure (e.g., Chambers et al ).…”
Section: Introductionmentioning
confidence: 99%
“…The addition of regularisation terms in inverse problem formulations is a powerful means of introducing prior information that has been proved to be essential for retrieving reliable solutions (Ellis and Oldenburg ). This has led to a variety of complementary techniques such as adding a smoothness constraint on the model to avoid unnecessary structure (e.g., Constable, Parker, and Constable ; deGroot‐Hedlin and Constable ), constraining the inverted model to a reference model (e.g., Oldenburg and Li ; Pidlisecky, Haber, and Knight ; Catt, West, and Clark ; Caterina et al ), using variable weighting factors depending on the reliability of prior information (Kim et al ), adding structural information such as known boundaries in the model (e.g., Kaipio et al ; Caterina et al ), decoupling the regularisation effects to preserve sharp boundaries where they are known to exist (Coscia et al ), or imposing bounds to the model resistivity values in selected regions by means of inequality constraints (Kim, Song, and Lee ; Cardarelli and Fischanger ). In the presented work, we implemented various modes of integrating a priori information, either by means of regularisation (as in all the previous references) or, alternatively, within the model and parameter mesh generation phase before the inversion process (Günther and Rücker ; Cardarelli and Fischanger ).…”
Section: Introductionmentioning
confidence: 99%
“…The topography of the survey area and the exact electrode location is usually included in the data inversion, as they are known to have a significant impact on the measured data [43][44][45][46][47][48]. It has also been shown that topographic features outside the actual survey area can impact upon the measured resistivity data and can lead to misinterpretation, especially in the case of 2D data analysis [49,50]. In the study presented here, the survey area is located within a 30 × 40 m excavation that is 10-35 m deep (Figure 3).…”
Section: Topographymentioning
confidence: 99%
“…The 2.5D inversion method (following references to 2D inversion imply the 2.5D assumption) assumes that the resistivity does not vary in the direction perpendicular to the vertical plane below the line. The perpendicular topographic variations of the embankment and chang-ing water levels to the side violate this assumption (Cho et al, 2014). As such, the data acquired from a 2D survey may be influenced by features adjacent to the survey, for example.…”
Section: Introductionmentioning
confidence: 99%